Oncologic Outcomes Associated with MRI-Detected Extramural Venous Invasion (mrEMVI) in Rectal Cancer: A Systematic Review and Meta-Analysis. Issue 5 (22nd January 2021) - Fournier, François Rouleau; Motamedi, Ali; Brown, Carl J.; Phang, Terry; Raval, Manoj; Hague, Cameron J.; Karimuddin, Ahmer A.
Abstract : Background: The role of MRI-detected EMVI (mrEMVI) as a reliable prognostic factor in rectal cancer has been emphasized in recent years but this finding remains underreported by many institutions. Objective: This review aimed to demonstrate the importance of pre- and post-treatment MRI-detected EMVI as independent prognostic factors of adverse oncologic outcomes in patients undergoing neoadjuvant therapy followed by total mesorectal excision. Methods: This review was designed using the PRISMA guidelines. The following electronic databases were searched from January 2002 to January 2020: CENTRAL, Ovid MEDLINE, PubMed and Ovid Embase. Main outcomes included disease-free survival (DFS) and overall survival (OS). Other outcomes of interest comprised positive resection margin and synchronous metastases. Results: Seventeen studies involving a total of 3821 patients were included for data synthesis. For pre-neoadjuvant treatment mrEMVI, pooled hazard ratio (HR) estimate for DFS was 2.30 (95%CI 1.54–3.44) for higher recurrence in mrEMVI-positive patients. mrEMVI-positive patients were found to have a lower OS with a pooled HR of 1.68 (95%CI 1.27–2.22). Pooled risk ratio (RR) for synchronous metastasis was 4.11 (95%CI 2.80–6.02) for mrEMVI-positivity. For post-neoadjuvant treatment EMVI (ymrEMVI), positive status showed a lower DFS with a pooled HR of 2.04 (95%CI 1.55–2.69). RR of having a positive resection margin status was 2.95 (95%CI 1.75–4.98) for ymrEMVI-positive patients. Conclusion: This review showed that oncologic outcomes are significantly worse for both pre- and post-neoadjuvant treatment mrEMVI-positive patients. MRI-detected EMVI should be consistently reported in rectal cancer staging and may provide guidance for the targeted use of additional systemic therapy. Abstract : Supplemental Digital Content is available in the text